Aplikasi Program Intel My Tip Pada PT. Digitas Solution - Yuda Prasetyo; Suwarni Suwarni (Universitas Respati Indonesia, 2018)
ABSTRAKPermasalahan yang ada pada Perusahaan Digitas Solution adalah banyaknya data yang diterima sehingga membuat sulitnya admin untuk malakukan penginputan data. Perusahaan yang bergerak dalam bidang komunikasi pemasaran (marketing communication services) dan pengembangan merek dagang (brand development) ini sedang membuat strategi pemasaran program Intel My Tip. Program Intel My Tip adalah program yang bertujuan untuk meningkatkan penjualan produk Intel dengan cara memberikan insentif kepada reseller atau partner yang telah menjual produk Intel yaitu Pentium dan Celeron di 6 kota besar di Indonesia. Dalam menjalankan program ini Digitas Solution mempunyai tim khusus Intel yang biasa disebut dengan Merchandiser, Merchandiser sangat berperan aktif dengan turun langsung ke lapangan, mensosialisasikan program Intel My Tip dan mengumpulkan data yang dibutuhkan, data yang dikumpulkan berupa bukti penjualan yaitu invoice dari setiap produk Intel yang terjual. Tujuan dari penelitian ini adalah merancang Aplikasi program Intel My Tip untuk membantu mengolah data penjualan partner dan bagian marketing dalam melihat poin yang sudah diraihnya serta dapat melakukan penukaran poin dengan reward secara online. Metodologi penelitian ini menggunakan metode System Development Life Cycle (SDLC) dengan model Waterfall. Kata kunci: Intel, Program My Tip, UML, reseller, partner ABSTRACT The problem that is in the Digitas Solution Company is the amount of data received, making it difficult for admin to input data. Companies that are engaged in marketing communication services and brand development are currently developing marketing strategies for the Intel My Tip program. The Intel My Tip program is a program that aims to increase sales of Intel products by providing incentives to resellers or partners who have sold Intel products namely Pentium and Celeron in 6 major cities in Indonesia. In carrying out this program Digitas Solution has a special Intel team commonly called the Merchandiser, Merchandisers play an active role by going directly to the field, socializing the Intel My Tip program and collecting the required data, data collected inthe form of sales receipts are invoices from each Intel product sold. The purpose of this study is to design the Intel My Tip program application to help process sales partner data and marketing departments in seeing the points that have been achieved and can exchangepoints with rewards online. The methodology of this research uses the System Development Life Cycle (SDLC) method with the Waterfall model. Keywords: Intel, Program My Tip,UML, reseller, partnerABSTRACT The problem that is in the Digitas Solution Company is the amount of data received, making it difficult for admin to input data. Companies that are engaged in marketing communication services and brand development are currently developing marketing strategies for the Intel My Tip program. The Intel My Tip program is a program that aims to increase sales of Intel products by providing incentives to resellers or partners who have sold Intel products namely Pentium and Celeron in 6 major cities in Indonesia. In carrying out this program Digitas Solution has a special Intel team commonly called the Merchandiser, Merchandisers play an active role by going directly to the field, socializing the Intel My Tip program and collecting the required data, data collected in the form of sales receipts are invoices from each Intel product sold. The purpose of this study is to design the Intel My Tip program application to help process sales partner data and marketing departments in seeing the points that have been achieved and can exchange points with rewards online. The methodology of this research uses the System Development Life Cycle (SDLC) method with the Waterfall model. Keywords: Intel, Program My Tip,UML, reseller, partner <w:LsdException Locked=